Two algorithms for computing the general component of jet scheme and applications. (November 2022) - Morán Cañón, Mario; Sebag, Julien
Abstract: Let k be a perfect field. Let X be an integral k -variety. Let m ∈ N . In this article, we study, from the theoretical and computational points of view, the component G m ( X ) of the jet scheme L m ( X ) defined to be the Zariski closure of the set of truncated arcs with a regular base-point. We prove that G m ( X ) can be described from any smooth birational model of X . When X is supposed to be affine embedded in A k N, this description allows us to provide an algorithm, valid in arbitrary characteristic, which computes a Gröbner basis of a presentation of G m ( X ) in A k ( m + 1 ) N from the datum of a given explicit smooth affine birational model of X . Then, we show how to use the datum of a presentation of G m ( X ) (in the suitable affine space) to deduce algebraic and geometric properties in two contexts from the theoretical and computational points of view. Firstly, we apply our main result to obtain bases for a class of homogeneous differential operators logarithmic along plane curves in arbitrary characteristics. Secondly, we introduce a motivic power series which encodes the geometry of all the G m ( X ) and prove its rationality in the specific case of homogeneous plane curve singularities thanks to our description of G m ( X ) via the normalization of X .